2016
DOI: 10.1159/000448628
|View full text |Cite
|
Sign up to set email alerts
|

Venous Thromboembolism in Primary Nephrotic Syndrome - Is the Risk High Enough to Justify Prophylactic Anticoagulation?

Abstract: Background: The reported incidence of venous thromboembolism (VTE) in patients with nephrotic syndrome (NS) varies widely, as does the approach to prophylactic anticoagulation. We aimed to assess the incidence of VTE in patients with primary NS in order to inform a sample size calculation to determine if a future clinical trial will ever be feasible. Methods: All adults undergoing native renal biopsy for NS between 2008 and 2013 yielding a diagnosis of primary glomerulonephritis were identified. Baseline serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 20 publications
2
26
0
1
Order By: Relevance
“…Though there is no guidelines or consensus on the prevention with anticoagulants in patients with nephrotic syndrome, but the study suggested the patients with nephrotic syndrome and combined with hypercoagulation should receive anticoagulants therapy to prevent thrombotic events. [ 15 ] We look forward to the well-powered clinical trials to be achieved.…”
Section: Discussionmentioning
confidence: 99%
“…Though there is no guidelines or consensus on the prevention with anticoagulants in patients with nephrotic syndrome, but the study suggested the patients with nephrotic syndrome and combined with hypercoagulation should receive anticoagulants therapy to prevent thrombotic events. [ 15 ] We look forward to the well-powered clinical trials to be achieved.…”
Section: Discussionmentioning
confidence: 99%
“…According to this defi nition several studies record a nearly 40-50% of unprovoked VTE in real life [5] and according to common thrombotic risk factors suggested by guidelines 2014; yet other clinical conditions are well known as conditions that may predispose for VTE as infl ammatory bowel disease, immunopathological disease and/or connectivitis, nephritic syndrome and others [10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…However, the literature does not offer the chance to understand the percentage of other medical condition associated to VTE as minor thrombotic risk factor such as infl ammatory bowel diseases [10], immunopathological disease/connectivitis [11], hormonal disease including hyperthyroidism [17] and so on.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 2 However, although the thrombotic risk is congruous across different samples and studies, the absolute risk estimates for thrombosis appear to vary by study cohort, both overall and by primary form of glomerulonephritis. 20 , 21 Risk also appears to vary by duration of NS, age, etiological glomerular condition (membranous nephropathy being highest risk), personal thrombosis history, degree of proteinuria, central venous catheterization, and coexisting maliganancy. 2 , 21 , 22 Thrombosis appears to be highest risk in the first 6 months of diagnosis or presentation; however, it may occur at any stage.…”
Section: Casementioning
confidence: 99%